2016
DOI: 10.1007/s12311-016-0813-x
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Atrophy in the Cerebellum—Evidence of Increased Vulnerability of the Crus and Vermis with Advancing Age

Abstract: This study examined patterns of cerebellar volumetric gray matter (GM) loss across the adult lifespan in a large cross-sectional sample. Four hundred and seventy-nine healthy participants (age range: 7-86 years) were drawn from the Brain Resource International Database who provided T1-weighted MRI scans. The spatially unbiased infratentorial template (SUIT) toolbox in SPM8 was used for normalisation of the cerebellum structures. Global volumetric and voxel-based morphometry analyses were performed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…What does vermian atrophy means in this context? The vermis is particularly vulnerable in the aging population ( Luft, 1999 ), since older adults show a higher degree of GM loss in the vermis, with a rate of GM loss of approximately 4.59% per decade, nearly double than over the cerebellum as a whole ( Yu et al, 2017 ). This finding is supported by anatomopathological data by Andersen et al that showed a selective reduction in the anterior lobe of the cerebellum corresponding to lobules I–V with age, with a 40% loss of Purkinje and granule cells and a 30% loss of global cortical volume selectively in the anterior lobe ( Andersen et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…What does vermian atrophy means in this context? The vermis is particularly vulnerable in the aging population ( Luft, 1999 ), since older adults show a higher degree of GM loss in the vermis, with a rate of GM loss of approximately 4.59% per decade, nearly double than over the cerebellum as a whole ( Yu et al, 2017 ). This finding is supported by anatomopathological data by Andersen et al that showed a selective reduction in the anterior lobe of the cerebellum corresponding to lobules I–V with age, with a 40% loss of Purkinje and granule cells and a 30% loss of global cortical volume selectively in the anterior lobe ( Andersen et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRI findings in abstinent alcoholics describe shrinkage of folia in the anterior superior vermis, notably lobules I‐V (eg,). By contrast, cerebellar volume shrinkage in normal aging occurs more inferiorly and posteriorly, in vermian lobules VI‐X, crus I‐II and vermian lobules Vi and VIIa, and lobules V‐VI . Thus, alcoholics who continue to drink or initiate dependent drinking later in life (cf) are at heightened risk for developing widespread cerebellar volume deficits with ramifications for extensive, cerebellar‐based performance deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Additional alcoholism and lesion studies report selective relations between performance on tasks assessing executive functions (Nakamura-Palacios et al, 2014; Sullivan, 2003; Sullivan et al, 2003), verbal working (Desmond et al, 2003), spatial memory (Chanraud et al, 2010), and learning and Crus I, Crus II, and lobule VI volumes (Schmahmann, 2019; Stoodley et al, 2016; Stoodley et al, 2012), whereas tests of gait and upright postural stability are often related to volumes of the anterior superior (I-IV) (Sullivan et al, 2000; Sullivan et al, 2006) and floccular-nodular (IX/X) lobules (Angelaki et al, 2010) unless cognitive information processing speed is also considered with gait speed (Nadkarni et al, 2014). By contrast, cerebellar volume shrinkage in normal aging occurs more inferiorly and posteriorly, in vermian lobules VI-X (Raz et al, 1998), Crus I-II and vermian lobules VI and VIIA (Yu et al, 2017), and lobules V-VI (Ziegler et al, 2012). Thus, alcoholics who continue to drink or initiate dependent drinking later in life (cf., Breslow et al, 2017; Sullivan et al, 2018) are at heightened risk for developing widespread cerebellar volume deficits with ramifications for cerebellar-based performance deficits.…”
Section: Introductionmentioning
confidence: 99%